Social workers and policy practice: (Re)Defining the role of social work on indigent policy design and implementation in South Africa - Molly Shayamano (International Review of Social Sciences Research)
This study examined the role of social workers in designing and implementing municipal indigent policies in South Africa. The study used qualitative research to assess social workers' roles in designing and implementing indigent policies. In addition, the study used a case study design, using the Buffalo City Metropolitan Municipality as a case study. Data was collected from extensive literature using documents from 2019 to 2025. Data was analysed using thematic analysis. This study revealed that the engagement of social workers in indigent policy design and implementation is very low, and this exclusion of social workers has led to limited advocacy for indigent policy change, failure to build effective coalitions, indigents' lack of awareness regarding the indigent policy, and exclusion of more deserving people in accessing indigent support. This study proposes that social workers be actively involved in the indigent policy implementation process, as they are highly skilled professionals able to deal with the most vulnerable community members. Within the indigent policy implementation process, social workers can play a significant role in municipal indigent policy development and evaluation by identifying and verifying indigents and advocating for indigents’ rights, ensuring they receive the support they are entitled to under indigent policies, such as counselling and psychosocial support.